Evaluation of Carer Contact Practices for Junction 17 CAMHS Inpatient Unit - Alaaelrahman Shahib; Ashley Cooper; Rebecca Dugard (BJPsych Open, 2025)
Aims: This audit aimed to assess and improve the consistency and quality of carer contact within the CAMHS inpatient ward at Junction 17. The objectives were to evaluate current communication practices against Trust policies, ensure effective documentation of carer interactions, and implement strategies to improve adherence to guidelines.